Investigation of Sorghum (Sorghum bicolor L.) Variety Preferences of Farmers in the Potential Low Land Areas of North Shewa Zone, Amhara Region - Yehuala Kassa; Demis Managido; Abiy Legesse; Teklemariam Ayele (Turkish Journal of Agriculture: Food Science and Technology)
Sorghum is one of the major staple crops grown in the poorest and most food-insecure regions of Ethiopia. Sorghum production is predominantly based on local seeds with limited use of commercial fertilizer or other chemicals. This study is therefore aimed to demonstrate the improved sorghum variety with its improved management practices and to assess farmers’ and extension workers’ reactions. The newly released variety of Beletew was evaluated with the variety of Melkam. The experiments were implemented using a simple plot design with farmers’ fields as a replicate. The result revealed that in both locations, the studied varieties showed nonsignificant variation in grain yield. Besides, all the participant farmers were agreed that the variety Beletew had compacted panicle, a larger number of spikes per panicle, stayed green character and yellow seed color. Similarly, about 78.3% and 65.6% of the participant farmers from Efratana gidim and Ensaro Districts respectively agreed that the variety Beletew had a larger panicle size than the variety Melkam and expected higher grain yields from it. Therefore based on the grain yield performance of the result of farmers’ evaluation, the new variety of Beletew was recommended to be pre-scale on a wider scale to sorghum-growing lowland areas as an alternative shortmatured varieties.